Au/AgI Dimeric Nanoparticles for Highly Selective and Sensitive Colorimetric Detection of Hydrogen Sulfide. (16th April 2018) - Zeng, Jingbin; Li, Min; Liu, Ao; Feng, Fan; Zeng, Teng; Duan, Wei; Li, Mengmeng; Gong, Mingfu; Wen, Cong‐Ying; Yin, Yadong
Abstract: The development of Au/AgI dimeric nanoparticles (NPs) is reported for highly selective colorimetric detection of hydrogen sulfide (H2 S). The detection mechanism is designed by taking advantage of the chemical transformation of AgI to Ag2 S upon reacting with sulfide, which leads to a shift in the plasmonic band of the attached Au NPs. The plasmonic shift is accompanied by a color change of the solution from purplish red to blue and finally to light green depending on the concentration of sulfide, thus enables a naked‐eye readout and UV–vis quantitation of the sulfide exposure. The Au/AgI dimeric NPs are further immobilized in agarose gels to produce test strips, which can be used for both naked‐eye readout and quantitative detection of sulfide using UV–vis spectroscopy thanks to its transparency in the visible region. Compared to commercial Pb(Ac)2 test papers, the agarose gel strip has superior performance for detecting sulfide in terms of sensitivity, selectivity, stability, and fidelity. The agarose gel is also capable of detecting gaseous H2 S at important concentration thresholds, suggesting its practicability in real life applications. The potential of agarose gels is further highlighted by its ability in the enrichment and colorimetric detection of gaseous H2 S released during cell cultivation. Abstract : A highly selective colorimetric method for sulfide detection is developed based on the unique dimeric structure of Au/AgI hybrid nanoparticles and their plasmonic shift during the chemical transformation of AgI to Ag2 S upon exposure to hydrogen sulfide.